A practical field trial to assess the potential of Sida hermaphrodita as a versatile, perennial bioenergy crop for Central Europe. (March 2019) - von Gehren, P.; Gansberger, M.; Pichler, Wilfried; Weigl, Martin; Feldmeier, Sabine; Wopienka, Elisabeth; Bochmann, Günther
Abstract: Due to high biomass accumulation ability and multiple ecological benefits, the versatile, perennial bioenergy crop Sida hermaphrodita has sparked the interest of researchers in Central Europe. We assessed the crop's agronomy and bioenergy potential when grown under Austrian climate and soil conditions. A field trial was established in Austria, where the factors planting density and utilization strategy (thermal or biogas) were monitored for three growing seasons. Harvesting lignified biomass for thermal utilization at the end of the growing period resulted in higher dry matter yields than green biomass for biogas utilization which was harvested with a two-cut strategy. Due to lower costs but similar yield, a planting density of 1.77 plants m -2 is preferable over 2.66 plants m -2 . The pelletizing process of the biomass was analyzed iteratively in 20 runs to optimize the energy efficiency and process stability while simultaneously increasing pellet durability. A simple drying step, disintegration with a pan grinder mill and pelletizing using a flat die pellet press resulted in stable, high quality pellets. Fuel characteristics of the biomass were favorable and all requirements to be categorized as solid biofuel were met, while combustion tests showed a good applicability of the produced pellets. When green biomass was used for biogas production, a significant drop in methane yield could be noted from the second growing season onward, indicating that older plants are less suitable for biogas production. Our results hint towards the potential of lignified S. hermaphrodita biomass to be used as a solid fuel for energy production. Highlights: Three year field trial to assess the potential of the energy crop S. hermaphrodita. Harvest of lignified biomass at the end of January reached highest yields. Pelletizing to produce high quality pellets with low energy consumption is possible. S. hermaphrodita pellets show good applicability and are suitable for use as fuel. Most energy efficient utilization of S. hermaphrodita biomass is its combustion as a solid fuel.